Psychological Violence on Early Age Children Reviewed from Family Type in Welahan Village, Jepara Regency - Saputri, Eka Yuni; Astuti, Henny Puji (Jurusan PGPAUD FIP UNNES, 2019)
This study aims to determine differences in psychological violence against early childhood in terms of family type. The violence that often occurs in early childhood is psychological violence. The perpetrators of violence against children are usually the closest people to the child, namely the family. In the child’s environment, children only know their families in 2 types of families; they are the nuclear family and extended family. This causes the forms of psychological violence against early childhood between the type of the nuclear family and large family to have differences. The formulation of the problem in this study is that there are differences in psychological violence against early childhood in terms of family type. The hypothesis of this study is that there are differences in psychological violence against early childhood living together with nuclear families and early childhood living together with extended families. This research is quantitative comparative research with research subjects of children aged 4-6 years. This research is conducted at TK (Kindergarten) Nurul Ulum and TK Sunan Muria in Welahan Village, Jepara Regency with 96 respondents. Data collection techniques in this study use the Psychic Hardness Scale for Early Childhood, with analysis using the Independent Sample t-Test method. The results of the study calculations using the Independent Sample t-Test get the value of tcount < ttable (-12.7786 < 1.985) and the value of sig. (2-tailed) < 0.05 (0.00 < 0.05), so there are differences in psychological violence towards early childhood in terms of family type. Based on the results of the study, psychological violence against early childhood who are living together with the nuclear family is higher compared to early childhood who lived with extended families.